2002
DOI: 10.1029/2002wr001340
|View full text |Cite
|
Sign up to set email alerts
|

Physical factors affecting the transport and fate of colloids in saturated porous media

Abstract: Saturated soil column experiments were conducted to explore the influence of colloid size and soil grain size distribution characteristics on the transport and fate of colloid particles in saturated porous media. Stable monodispersed colloids and porous media that are negatively charged were employed in these studies. Effluent colloid concentration curves and the final spatial distribution of retained colloids by the porous media were found to be highly dependent on the colloid size and soil grain size distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

31
545
10
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 672 publications
(590 citation statements)
references
References 40 publications
31
545
10
4
Order By: Relevance
“…These processes affecting particle transport are the same as those that influence solute transport, i.e., advection, diffusion, dispersion, and adsorption (Bradford et al, 2002). Particle motion along fluid streamlines is advection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These processes affecting particle transport are the same as those that influence solute transport, i.e., advection, diffusion, dispersion, and adsorption (Bradford et al, 2002). Particle motion along fluid streamlines is advection.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion of particles into porous media can result in more contact with the grains (Tufenkji and Elimelech, 2004). Bradford et al (2002) suggested that smaller particles are primarily removed by diffusive transport, while larger ones are removed by interception and sedimentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colloid attachment occurs due to the net interaction (i.e., summation of van der Waals forces and electrostatic double-layer forces) between colloidal and grain surfaces (DeNovio et al, 2004). Colloid straining, on the other hand, is the entrapment of colloids in pore throats and at grain-grain junctions which are too small to allow particle passage (Bradford et al, 2002).…”
mentioning
confidence: 99%
“…Their results indicate a distinction between irreversible deposited contact retardation and a reversible surface retardation with subsequent reentrainment after attachment. Straining due to trapping in the pore throats is another effect of particle retention; however this is not included in colloid attachment theory [22]. Although straining is obviously an important effect in quantitative filtration theory, it is not necessary to regard this effect for the investigation concerning the local deposition rate on a model sphere, where the particle position due to straining occurs everywhere on the model sphere with the same probability.…”
Section: Introductionmentioning
confidence: 99%